2019
DOI: 10.29252/jhsme.6.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spiritual-Religious Interventions on Increasing the Sense of Calmness and Forgiveness in Women Who Have Experienced Marital

Abstract: Background and Objectives: Marital infidelity can endanger the mental health of the victims and cause them to hate the cheating spouse; accordingly, it is necessary to identify and reinforce the factors that help relive this painful experience. Therefore, this study aimed to evaluate the effectiveness of spiritual-religious interventions on increasing the sense of calmness and forgiveness in women who have experienced marital infidelity. Methods: This quasi-experimental study was conducted based on a pretest-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Dilaporkan juga bahwa terdapat rasa optimis atau ketenangan serta kestabilan psikologis yang didapatkan oleh korban perselingkuhan dari spiritualitasnya. Disebutkan juga bahwa korban perselingkuhan yang mulanya ingin membalaskan dendam dan memiliki kebencian, tetapi dengan prakteknya pada spiritual keagamaan dapat mengurangi rasa tersebut serta meningkatkan rasa cinta dan kasih sayang (Naimi, 2019). Sebagai pembaruan, penelitian yang dilakukan saat ini memiliki tujuan yaitu untuk mengetahui apakah ada pengaruh antara religiusitas terhadap optimisme pada korban perselingkuhan.…”
Section: Pendahuluanunclassified
“…Dilaporkan juga bahwa terdapat rasa optimis atau ketenangan serta kestabilan psikologis yang didapatkan oleh korban perselingkuhan dari spiritualitasnya. Disebutkan juga bahwa korban perselingkuhan yang mulanya ingin membalaskan dendam dan memiliki kebencian, tetapi dengan prakteknya pada spiritual keagamaan dapat mengurangi rasa tersebut serta meningkatkan rasa cinta dan kasih sayang (Naimi, 2019). Sebagai pembaruan, penelitian yang dilakukan saat ini memiliki tujuan yaitu untuk mengetahui apakah ada pengaruh antara religiusitas terhadap optimisme pada korban perselingkuhan.…”
Section: Pendahuluanunclassified
“…Women tend to show more jealousy towards emotional affairs and men towards sexual affairs (6). Betrayed spouses may experience emotional, psychological, and physical problems to which they might show severe mental responses including anger, guilt, hopelessness, loss of trust, low self-esteem, and long depressive and anxiety episodes (7,8). Research has shown that couples with low emotional control suffer from many tensions in life roles (9,10).…”
Section: Introductionmentioning
confidence: 99%